1984
DOI: 10.1530/jrf.0.0710551
|View full text |Cite
|
Sign up to set email alerts
|

Variations in oxytocin, vasopressin and neurophysin concentrations in the bovine ovary during the oestrous cycle and pregnancy

Abstract: Bovine ovaries were obtained from the abattoir and corpora lutea were classified as: (1) early luteal phase (approximately Days 1-4); (2) mid-luteal phase (Days 5-10); (3) late luteal phase (Days 11-17); (4) regressing (Days 18-20) and (5) pregnant (Days 90-230). In addition, preovulatory follicles and whole ovaries without luteal tissue were collected. Concentrations of oxytocin, vasopressin, bovine neurophysin I and progesterone were measured in each corpus luteum by radioimmunoassay. Progesterone and neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
2
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 16 publications
2
37
2
1
Order By: Relevance
“…Additionally, there are some controversial issues regarding the interaction between OT and FSH, LH. Some early studies have shown that OT can inhibit the release of LH and FSH [25], whereas other reports have not [26,27]. In this research, OT plasma concentration was not correlated with that of LH and FSH.…”
Section: Discussioncontrasting
confidence: 75%
“…Additionally, there are some controversial issues regarding the interaction between OT and FSH, LH. Some early studies have shown that OT can inhibit the release of LH and FSH [25], whereas other reports have not [26,27]. In this research, OT plasma concentration was not correlated with that of LH and FSH.…”
Section: Discussioncontrasting
confidence: 75%
“…Thus, the increase of the OT concentrations in bovine CL from the early to the mid-luteal phase ( Fig. 1) is maintained only by the stimulation of a post-translational oxytocinneurophysin process [15][16][17][18]. The terminal enzyme in the post-translating processing of oxytocinneurophysin is peptidyl glycine α-amidating mono-oxygenase (PGA) [13,17].…”
Section: Luteotropic Role Of Luteal Oxytocinmentioning
confidence: 99%
“…C'est la progestérone qui, jusqu'à maintenant, a été l'unique «révélateur» de l'activité lutéale par les variations de sa concentration dans le plasma sanguin (Terqui et André, 1982;Humblot et Thibier, 1984;Kishimoto et al, 1987) et dans le lait (Laing et Heap, 1973;Heap et al, 1976;Hoffman et al, 1976;Cox et al, 1978;Booth et al, 1979;Thibier, 1980;Laitinen et al, 1985;Sauer et al, 1986;Stanley et al, 1986; Van de Wiel et Koops, 1986 (Humblot et al, 1987). Par ailleurs, malgré leur apparente simplicité, les kits EIA peuvent parfois exiger des temps de réaction de 20!0 min pour que la lecture soit interprétable (Tainturier et al, 1988 (Mialot, 1988) (Wathes et al, 1984;Ivell et al, 1985).…”
unclassified